Sustainability Goals in Economic Policy — Economic Considerations - Achim Wambach; Christine Zulehner (Wirtschaftsdienst)
Abstract Through the canon of the UN SDGs or the European Green Deal, sustainability goals are finding their way into legislation. From an economic point of view, these targets often aim to reduce negative external effects, which is in many cases in line with the economic goal of maximising welfare. The determination of welfare gains in this context is not trivial and raises new questions in economics. Because they are often not clearly defined, the anchoring of sustainability goals in legislation may weaken legal certainty and lead to an abusive pursuit of other goals under their guise. This should be prevented by formulating the goals as concretely and legally securely as possible and by building up competence in the authorities entrusted with their implementation.